2018
DOI: 10.1093/aob/mcx198
|View full text |Cite
|
Sign up to set email alerts
|

Strong population bottleneck and repeated demographic expansions of Populus adenopoda (Salicaceae) in subtropical China

Abstract: Chloroplast data and SDMs suggest that P. adenopoda might have survived in multiple glacial refugia in central and southern parts of its range during the LGM. Populations of the Yunnan-Guizhou Plateau in the southern part have high chloroplast DNA diversity, but may have contributed little to the postglacial recolonization of northern and eastern parts. The three major demographic events inferred by DIYABC coincide with the initiation of the LIG, start of the LGM and end of the LGM, respectively. The species m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 82 publications
1
20
0
Order By: Relevance
“…Fragment sizes were read with the GeneMapper version 4.0. CERVUS [32] was used in eliminating four loci as existing null alleles (F (Null) > 0.4) [33]. PCR products by three cpDNA intergenic spacers were sequenced in both directions by Sangon Biotech Services Company Ltd. (Shanghai, China).…”
Section: Dna Extraction Pcr Amplification and Sequencingmentioning
confidence: 99%
“…Fragment sizes were read with the GeneMapper version 4.0. CERVUS [32] was used in eliminating four loci as existing null alleles (F (Null) > 0.4) [33]. PCR products by three cpDNA intergenic spacers were sequenced in both directions by Sangon Biotech Services Company Ltd. (Shanghai, China).…”
Section: Dna Extraction Pcr Amplification and Sequencingmentioning
confidence: 99%
“…A substantially different modeled LIG distribution compared with those during the present interglacial period is not unique to the Emei mustache toad. Around the Sichuan Basin, such results have been commonly obtained for various animal [49,50,[68][69][70][71] and plant groups [45,55,72,73]. Because the LIG period at1 40-120 ka is relatively recent on an evolutionary scale, it is unlikely that the corresponding effects have been erased.…”
Section: Climatic Suitabilitymentioning
confidence: 86%
“…Different studies showed that spatial separation of Populus spp. populations is governed by historical processes, mainly by events in the Pleistocene and Holocene (Keller et al, 2010;Macaya-Sanz et al, 2012;Dewoody et al, 2015;Meirmans et al, 2017;Fan et al, 2018). Therefore, the variability of P. laurifolia population structure in the Tom River basin is the subject for a further extended research.…”
Section: Discussionmentioning
confidence: 99%